2017
DOI: 10.1123/jcsp.2014-0049
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Affectivity, and Alexithymia in Scuba Diving: Two Types of Risk Taking

Abstract: Objectives for this study were, first, to describe individual differences in risk taking among scuba divers. Differences were examined on personality dimensions and psycho-affective variables, including positive and negative affect, as well as alexithymia. In addition, the study examined contributors to two types of behavior associated with scuba diving—deliberate risk taking and controlled participation in a high-risk sport (non-risk-taking). A cross-sectional design was used, and 131 participants were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…The high-risk environment is at the center of research involving alexithymia in sport. Theories suggest that this environment would provide the benefits of regulating emotions and, thus, experience and mastering anxiety, which can be particularly beneficial [ 14 , 37 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The high-risk environment is at the center of research involving alexithymia in sport. Theories suggest that this environment would provide the benefits of regulating emotions and, thus, experience and mastering anxiety, which can be particularly beneficial [ 14 , 37 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, various studies have shown that alexithymia would be a potential moderator of anxiety fluctuations since there is greater anxiety in alexithymic athletes than in the non-alexithymic [ 8 , 10 ]. In high-risk sports, theories suggest that this environment would provide benefits of regulating emotions and thus experiencing and mastering anxiety, which can be particularly beneficial [ 9 , 11 , 13 , 14 , 15 ]. Here we observed less anxiety in the competition group and a significant positive relationship was found between the number of hours practiced and the competitive sport practice.…”
Section: Discussionmentioning
confidence: 99%
“…In high-risk domains, alexithymics are in a better position to push themselves to their physical limits and thus alexithymic prevalence is markedly higher than in the general population, reaching 30% in scuba-diving, climbing, skydiving, sea-rowing, mountaineering, and rowing [ 8 , 9 , 10 , 11 , 12 ]. Theories suggest that the high-risk environment would provide benefits of regulating emotions and thus experience mastering anxiety, which can be particularly beneficial to alexithymic sports practitioners [ 9 , 11 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Equally, research has shown that individuals high in alexithymia can glean emotion regulation benefits via other, more adaptive, means. Specifically, researchers have found that high-risk sports (Bonnet et al, 2017;Panno et al, 2019;Woodman et al, 2010) offer a particularly fertile emotion regulation framework for individuals high in alexithymia (Woodman et al, 2009). Fenichel's (1939) work on the counter-phobic attitude provides the groundwork for a potential explanation as to why individuals may receive an anxiolytic benefit from high-risk sports.…”
Section: Alexithymia and The Anxiolytic Effect Of Endurance Runningmentioning
confidence: 99%